1998
DOI: 10.1097/00006454-199808000-00012
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of astrovirus diarrhea of infancy in Mexico City

Abstract: Astrovirus was associated with 5% of the episodes of diarrhea in this cohort of young Mexican children and presented as a mild secretory diarrhea. Five predominant antigenic types were detected with type 2 being the most common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
57
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 23 publications
7
57
0
1
Order By: Relevance
“…This appeared to be irrespective of whether the virus had been detected via the genome or by enzyme immunoassay (3,16,18,19). The incidence was lower than that generally found in studies in developing countries (5,6,8,13). Astrovirus infection usually shows annual winter peaks in studies carried out in temperate climates (14) and, based on the results of the 1995 to 1998 survey period, this is possibly also the case in central Australia, with 1996 perhaps having been an unusual year.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This appeared to be irrespective of whether the virus had been detected via the genome or by enzyme immunoassay (3,16,18,19). The incidence was lower than that generally found in studies in developing countries (5,6,8,13). Astrovirus infection usually shows annual winter peaks in studies carried out in temperate climates (14) and, based on the results of the 1995 to 1998 survey period, this is possibly also the case in central Australia, with 1996 perhaps having been an unusual year.…”
Section: Discussionmentioning
confidence: 76%
“…In developing countries the incidence has often been higher, ranging up to 26% of all children with diarrhea in a study of a Mayan community (5,6,8,13). Surveys have also shown that serotype 1 is the most frequently detected diarrheacausing type, with serotypes 2, 3, 4, and 5 being less common (11,16,18,19).…”
mentioning
confidence: 99%
“…These results agree with those from a study carried (AG) in relation to the period of year (1994-1996 and 1998-2001) out by López et al (2000) which analyzed children up to ten years from Spain. Studies have shown that astroviruses occur preferentially during the colder months of the year (Phan et al 2004, Galdiero et al 2005) even though other investigations have shown a higher viral incidence during warmest months (Guerrero et al 1998, Naficy et al 2000. Other studies report a year-round occurrence of astroviurs infection (Schnagl et al 2002, Giordano et al 2004.…”
Section: Discussionmentioning
confidence: 98%
“…Subject -The study was performed using 1244 fecal samples collected from hospitalized children at public hospitals in the cities of Goiânia, Goiás (1998 and Brasília, Distrito Federal (1994to 1996and 1998, aged up to five years. Of these, 1041 samples were from children with acute diarrhea (AG) which was defined as three or more liquid or semiliquid evacuations per day, and 203 from non-diarrheic children; 743 samples were from children from Goiânia-GO (699 with AG and 44 without AG) and 501 from children living in Brasília-DF (342 with AG and 159 without AG).…”
Section: Methodsmentioning
confidence: 99%
“…Human astroviruses (HAstV) have been found to be the second leading cause of acute viral gastroenteritis in young children worldwide, generally responsible for around 4 to 8% of cases (4,8,9,20), although incidences as high as 26% in isolated populations have been reported (15). The HAstV particles are formed by a nonenveloped capsid protein and a polyadenylated positive-strand RNA genome of approximately 7 kb (10,25).…”
mentioning
confidence: 99%